Comparative study of various methods of fetal weight estimation at term pregnancy in a tertiary hospital in Kanchipuram, Tamil Nadu, India - K., Parvathavarthini; C., Santhanalakshmi; Prasad, Geetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Prediction of fetal weight is one of the methods towards effective management of pregnancy and delivery. Ultrasonography is the standard method to monitor the weight, but in the absence of such facility it becomes difficult particularly in the primary care setting. Clinical methods can be considered as an option and this requires selection of the valid method in deriving the fetal weight. In the present study, an effort is made to compare two different clinical methods and USG and relate to the actual weight of the baby at birth. Methods: One hundred pregnant women satisfying the criteria, consenting for the study were recruited. Both USG and clinical methods were done and estimated the fetal weight. Weight of the baby at birth was measured. Results: All the three methods had significant relationship with the baby weight. Results indicated that estimation of fetal weight by Dare’s formula could predict 69% of the cases correctly followed by Johnson’s method which could predict 61% of the cases correctly. USG predicted 67% of the cases correctly. Percentage error was least with USG and the standard deviation of error was lower with Dare’s formula. Conclusions: It can be concluded that Dare’s formula of clinical methods can be a potential option to be promoted in predicting the fetal weight in the absence of USG facilities. Training in this method is very important and can be an integral part in managing pregnancy during delivery in primary care setting.